Exploring English Language Teachers’ Technological Competence in Listening Skills Instruction (NOBEL: Journal of Literature and Language Teaching, 2023)
The digitalized educational landscape of today requires ELT teachers to be conversant with technology. This study examined ELT teachers’ technological and pedagogical knowledge and their use of technology in listening skills instruction. To this end, an exploratory qualitative research design was employed. Thematic analysis was used to analyze the data collected using classroom observation and interviews. N-Vivo version 10 software was used for the data analysis. The findings indicated that teachers have a fair command of technology. However, they had limited technological content knowledge and technological pedagogical knowledge (TPK). Teachers were not able to make use of their knowledge of technology in their teaching. During listening instructions, only a few teachers use a smart board or a laptop to play audio materials. Most are not familiar with how to use any digital gadgets for teaching. For successful integration of digital technologies into listening instruction, training in the TPK is recommended. Furthermore, teachers’ capacity to use relevant digital apparatuses should be built.